Contribuições do mestrado profissional para a prática pedagógica do professor de biologia - Santana, Tainan Amorim (2018)
The master’s profissional program is one formation modality continued of teachers on the Public Political that aim the improvement of the Basic Educacion. The qualitative approach research aim to understand the contributions of the master’s profissional course in teaching Science and Math of UFPA on the improvement of the pedagogical practice of the Science/Biology teacher. The research of qualitative approach and exploratory character, was developed on the Federal University of Pará, on the master’s profissional course in guideline in science and math teaching of the UFPA, with the graduated students in Biological Science/Teaching. Therefore, document analysis, questionaries and interview were realized to have access to the information that aim to identify and analyse what the studens-teachers know about the master’s profissional program, your motivations to choose the course, and your contributions to improve your pedagogical practice. One questionary was apply with the coordenation of the master’s profissional program in guideline science and math teaching of UFPA, to cognize the political aspects that influenced on the implementacion of the course. Beside that, all the dissetacions already defended by the students-teachers were read and analized, with the object to know your researchs, the impacts of them in the practice and your impressions about the experinence offered by the program provided to this students- teachersresearchers. All the datas were analysed through categories, that were observed by the light of the referencial teorical. The first category refers to "teacher training". Given the data, it was noticed that the program contributed significantly in the formation of the reflective teacher and researcher, stimulating the student-teacher to always study, reflect, research and improve their practice. The second category was "Professional Master's Degree" which portrayed the Program's Master's Degree in Science and Mathematics Education on the emergence of the Program, its profile and in greater detail. The third category refers to the "Curriculum". Through it, the curricular composition of the Program was analyzed, verifying not only the disciplines that compose it, but also the implications of all its structure in the formation of these students-teachers. Through it, the curricular composition of the Program was analyzed. On that, we identify the contributions of theses programs, because changes of posture were evidenced, the student-teachers showed themselves with a remarkable reflexive posture that provided changes in their pedagogical practice, the proposals of your implamtacion, limitacions and your reflection on the school reality of these studens-teachers.